Mycosis fungoides - case presentation - Laura Statescu; Dan Vata; Laura Gheuca Solovastru (Our Dermatology Online, 2014)
Mycosis fungoides (MF) is a neoplastic disease of the lymphoreticular system with substrate of T lymphocyte hyperplasia and multifactorial etiology. Usual onset is around age 50, with skin lesions, and in advanced stages affects the internal organs. Mycosis fungoides has specific histological feature: polymorphous infiltrate located in the papillary dermis which ends abruptly in the middle dermis.